2014
DOI: 10.1039/c4cc00452c
|View full text |Cite
|
Sign up to set email alerts
|

A fluorescent light-up probe with AIE characteristics for specific mitochondrial imaging to identify differentiating brown adipose cells

Abstract: We report the design and synthesis of a specific mitochondrial fluorescent probe AIE-MitoGreen-1 with AIE characteristics to monitor the mitochondrial morphology changes and identify the differentiation process of living brown adipose cells. The probe AIE-MitoGreen-1 has significant advantages such as high cellpermeability, good mitochondrial retention, low background fluorescence, large Stokes shift, and low toxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
80
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 103 publications
(81 citation statements)
references
References 19 publications
1
80
0
Order By: Relevance
“…Confocal images showed that the probe could specially localize in mitochondria with bright blue emission, which Scheme 9 Chemical structure of the TPE-4Lac probe and schematic illustration for cholera toxin detection. 45 The probe utilised a salicylaldazine fluorophore with both AIE and ESIPT nature attached with two pyridinium groups for targeting mitochondria (Scheme 10). 9B-D).…”
Section: Mitochondria Trackingmentioning
confidence: 99%
“…Confocal images showed that the probe could specially localize in mitochondria with bright blue emission, which Scheme 9 Chemical structure of the TPE-4Lac probe and schematic illustration for cholera toxin detection. 45 The probe utilised a salicylaldazine fluorophore with both AIE and ESIPT nature attached with two pyridinium groups for targeting mitochondria (Scheme 10). 9B-D).…”
Section: Mitochondria Trackingmentioning
confidence: 99%
“…27 Moreover, excited-state intramolecular proton transfer (ESIPT) mechanism was further introduced to AIE fluorogens, which allowed the development of light-up probes with 4 sharp imaging contrast, high signal-to-noise ratios and extremely large Stokes shifts. [28][29] In this contribution, we report a small apoptosis probe AIE-ZnDPA based on zinc coordination and salicylaldazine fluorophore skeleton. 30 The synthetic routes to AIE-DPA and AIE-ZnDPA are shown in Scheme S1.…”
Section: Introductionmentioning
confidence: 99%
“…As MMP-dependent mitochondrial probes, these dyes are potentially applicable in tracking mitochondria for apoptosis studies, [23] identifying the differentiating brown adipose cells, [24] and evaluating sperm activity. [22] Moreover, it has been reported recently that most cancer cell lines exhibit a much higher MMP than normal cancer lines.…”
Section: Cancer Cell-targetingmentioning
confidence: 99%